New Research Directions in Popular Education: Towards a Reconceptualization of the Field - Elizabeth Lange; Peter Mayo; Angela Miles; Daniel Schugurensky (Adult Education Research Conference, 2000)
In this roundtable, departing from traditional popular education theory and practice, four panelists share findings of their research in progress, and pose questions to stimulate the current debates on popular education.